2019
DOI: 10.18535/ijmsci/v6i12.03
|View full text |Cite
|
Sign up to set email alerts
|

Acquired neuromuscular weakness In Intensive Care Unit: Review article

Abstract: A substantial number of patients admitted to the ICU because of an acute illness, complicated surgery, severe trauma, or burn injury will develop a de novo form of muscle weakness during the ICU stay that is referred to as "intensive care unit acquired weakness" (ICUAW). This ICUAW evoked by critical illness can be due to axonal neuropathy, primary myopathy, or both. Underlying pathophysiological mechanisms comprise microvascular, electrical, metabolic, and bioenergetic alterations, interacting in a complex wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…However, direct muscle injury caused by COVID‐19 has been reported in some viral infections, such as influenza, 45 human immunodeficiency virus 46 and SARS, 34 but studies have not proven direct muscle injury induced by the virus. Studies have shown that microvascular, electrical, metabolic, and bioenergetic changes interact in complex ways and cause muscle weakness or atrophy 47 . According to the present study, it is not possible to determine the effects of the disease on different muscle types.…”
Section: Discussionmentioning
confidence: 65%
“…However, direct muscle injury caused by COVID‐19 has been reported in some viral infections, such as influenza, 45 human immunodeficiency virus 46 and SARS, 34 but studies have not proven direct muscle injury induced by the virus. Studies have shown that microvascular, electrical, metabolic, and bioenergetic changes interact in complex ways and cause muscle weakness or atrophy 47 . According to the present study, it is not possible to determine the effects of the disease on different muscle types.…”
Section: Discussionmentioning
confidence: 65%